2012
DOI: 10.3109/09553002.2012.652725
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of extremely low frequency magnetic field-induced motor behavior changes in Mongolian gerbils of different age

Abstract: It can be proposed that the specific temporal patterns of ELF-MF-induced motor behavior changes in 3- and 10-month-old gerbils are a consequence of age-dependent morpho-functional differences in the brain structures responsible for a control of motor behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Results revealed that the EMF group had lowest total distance traveled and movement velocity in the Open field test. These results are in line with previous studies (Balassa et al, 2009b;Balind et al, 2014b;Janać et al, 2012b), that assessed that 48 h of exposure to 50 Hz low-frequency EMF on the motor activity of insects. They concluded that their motor activity was reduced (Balind et al, 2014b).…”
Section: Open-field Testsupporting
confidence: 93%
See 1 more Smart Citation
“…Results revealed that the EMF group had lowest total distance traveled and movement velocity in the Open field test. These results are in line with previous studies (Balassa et al, 2009b;Balind et al, 2014b;Janać et al, 2012b), that assessed that 48 h of exposure to 50 Hz low-frequency EMF on the motor activity of insects. They concluded that their motor activity was reduced (Balind et al, 2014b).…”
Section: Open-field Testsupporting
confidence: 93%
“…They concluded that their motor activity was reduced (Balind et al, 2014b). Another study investigated the effect of low‐frequency EMF on changes in the motor behavior of different age rats (Janać et al, 2012b). Their findings showed that in three‐month‐old rats, exposure to EMF increased their motor activity (in contrast to our findings, whereas in the 10‐month‐old rats, it reduced motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Its influence on ionic currents and pumps [34]–[36], neurotransmission [37][43] and behaviour [42], [44][52] has been well documented. This influence could be achieved through interaction of ELF-MF with chemical bonds between adjacent atoms leading to change in reaction between biomolecules [53] and disruption of biomembrane changing structure of its protein molecules [54].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results have shown that ELF‐MF, among others, has influence on motor behavior (Janać et al, ; Rauš et al, ), oxidative stress parameters in the brain (Jelenković et al, ; Selaković et al, ), the affinity and density of serotonin receptors in the prefrontal cortex (Janać et al, ). Having in mind that central control of GC secretion is regulated by neurosecretory neurons in the hypothalamic PVN we wanted to explore what influence ELF‐MF could have on ACTH cells.…”
Section: Introductionmentioning
confidence: 99%